Hypoxia-inducible Factor 2α: A Key Player in Tumorigenesis and Metastasis of Pheochromocytoma and Paraganglioma? - Bechmann, Nicole; Eisenhofer, Graeme (Experimental and Clinical Endocrinology & Diabetes, 2021)
Germline or somatic driver mutations linked to specific phenotypic features are identified in approximately 70% of all catecholamine-producing pheochromocytomas and paragangliomas (PPGLs). Mutations leading to stabilization of hypoxia-inducible factor 2α (HIF2α) and downstream pseudohypoxic signaling are associated with a higher risk of metastatic disease. Patients with metastatic PPGLs have a variable prognosis and treatment options are limited. In most patients with PPGLs, germline mutations lead to the stabilization of HIF2α. Mutations in HIF2α itself are associated with adrenal pheochromocytomas and/or extra-adrenal paragangliomas and about 30% of these patients develop metastatic disease; nevertheless, the frequency of these specific mutations is low (1.6–6.2%). Generally, mutations that lead to stabilization of HIF2α result in distinct catecholamine phenotype through blockade of glucocorticoid-mediated induction of phenylethanolamine N-methyltransferase, leading to the formation of tumors that lack epinephrine. HIF2α, among other factors, also contributes importantly to the initiation of a motile and invasive phenotype. Specifically, the expression of HIF2α supports a neuroendocrine-to-mesenchymal transition and the associated invasion-metastasis cascade, which includes the formation of pseudopodia to facilitate penetration into adjacent vasculature. The HIF2α-mediated expression of adhesion and extracellular matrix genes also promotes the establishment of PPGL cells in distant tissues. The involvement of HIF2α in tumorigenesis and in multiple steps of invasion-metastasis cascade underscores the therapeutic relevance of targeting HIF2α signaling pathways in PPGLs. However, due to emerging resistance to current HIF2α inhibitors that target HIF2α binding to specific partners, alternative HIF2α signaling pathways and downstream actions should also be considered for therapeutic intervention.
Keywords: genotype-phenotype relationships; HIF2α inhibitors; hypoxia; invasion-metastasis cascade; neuroendocrine-to-mesenchymal transition